Early Identification of Risk Factors for Mobility Decline Among Hospitalized Older Patients. (August 2019) - Lee, Yejin; Lee, Hyun-Haeng; Uhm, Kyeong Eun; Jung, Ho Joong; Kim, Yoon-Sook; Shin, Jinyoung; Choi, Jaekyung; Han, Seol-Heui; Lee, Jongmin
Abstract : Objective: The aim of the study was to identify the risk factors for mobility decline among hospitalized older patients early. Design: This is a prospective cohort study. A total of 875 older patients were divided into two groups: older patients with and without mobility decline. The mobility level was measured using the item of functional mobility in the Geriatric Screening for Care 10. The change in mobility between admission and discharge was determined as the dependent variable. There were a total of 18 independent variables, which consisted of three demographic variables, 10 most problematic domains of geriatric care, and five other health-related variables. A multivariable logistic regression analysis was conducted to identify the risk factors for mobility decline during hospitalization. Results: Of the 875 older patients, 135 (15.4%) experienced mobility decline during hospitalization. The multivariable logistic regression analysis revealed female sex, cognitive impairment, and underweight as the risk factors for mobility decline during hospitalization. Conclusions: The identified risk factors should be considered to identify patients at a risk of mobility decline early and to provide targeted interventions, which can prevent mobility decline. Abstract : Supplemental digital content is available in the text.